2012
DOI: 10.3390/ijms131114606
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Nitric Oxide and Asymmetric Dimethylarginine in Pregnancy and Fetal Programming

Abstract: Nitric oxide (NO) regulates placental blood flow and actively participates in trophoblast invasion and placental development. Asymmetric dimethylarginine (ADMA) can inhibit NO synthase, which generates NO. ADMA has been associated with uterine artery flow disturbances such as preeclampsia. Substantial experimental evidence has reliably supported the hypothesis that an adverse in utero environment plays a role in postnatal physiological and pathophysiological programming. Growing evidence suggests that the plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 101 publications
(127 reference statements)
3
52
0
Order By: Relevance
“…These conditions can cause increased oxidative stress either in the mother or the fetus, which may result in the programming of diseases in the offspring at a later stage [58,66]. …”
Section: Redox and Epigenetic Mechanisms In Fetal Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…These conditions can cause increased oxidative stress either in the mother or the fetus, which may result in the programming of diseases in the offspring at a later stage [58,66]. …”
Section: Redox and Epigenetic Mechanisms In Fetal Programmingmentioning
confidence: 99%
“…Maternal adversities leading to dysregulation of placental development originated from preimplantation affecting the course of pregnancy were shown in both animal and human studies to alter the epigenetic process (e.g., DNA methylation, histone modifications, and genome imprinting) and result in preeclampsia and dismal fetal outcomes [66,69]. A recent study showed altered global DNA methylation patterns in preeclampsia placentas and its association with blood pressure [129].…”
Section: The Roles Of Melatonin In Compromised Pregnanciesmentioning
confidence: 99%
“…Among the guanidine compounds listed as uremic toxins [2], ADMA and SDMA and have been increasingly recognized as putative toxic non-proteinogenic amino acids in a wide range of human diseases over the past decades [3,4,5,6,7,8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Given that NO has pleiotropic bioactivities, it is not surprising that a variety of important biological functions are regulated by ADMA and SDMA. Emerging clinical and experimental evidence indicates that ADMA and SDMA are involved in the pathophysiology of endothelial dysfunction [13], atherosclerosis [4], oxidative stress [14,15], inflammation [16,17], uremia [8], apoptosis, [18], autophagy [19], and impaired immunological function [20]. …”
Section: Introductionmentioning
confidence: 99%
“…Maternal plasma NO regulates feto-placental vascular activity and placental flow [3]. The activity of constitutive NO synthase is dependent on ADMA.…”
Section: Discussionmentioning
confidence: 99%